Objektifikasi Perempuan dalam Iklan Televisi : Analisis Lintas Budaya terhadap Iklan Parfum Axe yang Tayang di Televisi Indonesia dan Amerika Serikat (Jurnal Kajian Media, 2017)
This research is concerned with the objectification of women in the television advertisement. I employ qualitative methodology (critical discourse analysis) to highlight how sexist media construct objectified images of feminine. This research analyzes the content of television advertisements from Axe fragnance in Indonesia and the U.S to know how beauty is encoded in terms of sexual portrayal. These findings suggest that beauty in the western perspective, may be constructed more in terms of the body. This study also discusses how feminist critiques of the sexual objectification of women in advertising may need to be considered within Eastern perspective. I argue that the image of an ideal woman, as presented in advertisements of Axe fragrance, relegates women to objects of desire, leisure and sex. Keywords: Women objectification, feminim, critical discourse analysis, capital